La autoría mediata por instigación en la realidad jurídica ecuatoriana. - Anchatuña Laica, Esteban Daniel (2023)
Mediate authorship has been recognized in the criminal legal framework of Ecuador in different articles that refer to its procedure in this regard. The objective of this investigation was to analyze through the bibliographic review the legal norm of Ecuador to determine the correct application of the criminal figure of mediate authorship by instigation in the legal reality of the country from the studied doctrine. The population involved were 30 lawyers and judges with experience in the criminal field, of which a total of 24 of them were selected, through an intentional non-probabilistic sampling, endorsed by the willingness to participate in the investigation, to make up the sample of the investigation. present investigation. The use of different scientific methods made it possible to appreciate that the analysis of the essential doctrinal and legal points that include mediate authorship by instigation, as well as its relevance in the application of the criminal legal figure of mediate authorship by instigation in the legal reality of the Ecuador, show the existence of fundamental aspects that allow elucidating between a case of mediate authorship or instigation. The first, based on the instrumentalization of the executor, where it released from all debts for having been instrumentalized; since, the mediate author will possess the domain of the fact, will or functional. Meanwhile, in cases of instigation, responsibility is not shifted to the operator, as there are no evidences of instrumentalization. Here, the operator is the fundamental element, since he is the one who has control of the media and has the last word.